Global Regulatory Challenges in The Aesthetic Beauty Clinic Business - Siska Diana Sari (Kertha Patrika, 2025)
Regulation of beauty clinic is very important to maintain patient’s safety and wellbeing. In addition, it also involves physician and beautician licensing and certification. This regulation is intended to ensure competency and commitment to patient’s health and safety, and beauty clinic should comply with the legal requirement for its operation, including getting licensing and certification needed, attending appropriate sanitation and cleanliness practices, ascertaining the safety of equipment and product used, and protecting patient’s privacy and confidentiality. This regulation also helps maintain reputation and trust in beauty clinic business entirely. Incompliance with regulation results in the unlawful action. The states in the world should protect the patients of esthetic beauty clinic as the form of law guaranty and certainty as well as justice.